La concretezza dell’amore. L’attualità delle Opere di Misericordia - Mariani, Andrea (Alpha Omega, 2017)
Summary: “It is my most fervent desire that the Christian people reflect upon the corporal and spiritual works of mercy during the Holy Year” (Misericordiae vultus, n. 15). This is what Pope Francis writes in the Bull of proclamation of the Extraordinary Holy Year of Mercy. The Bible asserts: “God is love” (1 Jn 4, 8). Hence, mercy is not just one of the many attributes of God, but belongs profoundly to his very nature. Indeed, God does not love; but he is Love; God is not merciful, but he is Mercy. Mercy is God’s identity card. Nowadays, we are all called to proclaim that God is mercy. To believe in him means to practise acts of love. This is where we see the relevance of the corporal and spiritual works of mercy. Every person, created in the image and likeness of Mercy, cannot but be in turn a concrete expression of Mercy. Key words: works of mercy, Extraordinary Holy Year of Mercy, God is Love, love of neighbour, Pope Francis. Parole chiave: opere di misericordia, Giubileo Straordinario della Misericordia, Dio è Amore, amore al prossimo, Papa Francesco.